1997
DOI: 10.1021/jf970187m
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Characterization of Betanine Oxidation Catalyzed by Horseradish Peroxidase

Abstract: Horseradish peroxidase (HRP, EC 1.1.11.7) catalyzed oxidation of betanine is complex, as judged by the shape of the consecutive absorption spectra of the reaction medium. Graphic analysis of these spectra by a matricial test revealed the presence of at least three kinetically related absorbent species in the reaction mixture. Analysis by HPLC confirmed the presence of several reaction products. During the course of the reaction, a red intermediate and several yellow products, presumably of a polymeric nature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…Oxidation products of betanin by MPO are not known. Products from the reaction between betanin and horseradish peroxidase have been described as stable phenoxyl radicals and betalamic acid [43], however, we failed to have any spectral evidence of such compounds in our system. It is tempting to speculate that a rapid reaction of betanin and/or MPO-oxidised betanin with NO z 2 led to the accumulation of end-products that do not exhibit a characteristic absorbance spectrum.…”
Section: Discussionmentioning
confidence: 61%
“…Oxidation products of betanin by MPO are not known. Products from the reaction between betanin and horseradish peroxidase have been described as stable phenoxyl radicals and betalamic acid [43], however, we failed to have any spectral evidence of such compounds in our system. It is tempting to speculate that a rapid reaction of betanin and/or MPO-oxidised betanin with NO z 2 led to the accumulation of end-products that do not exhibit a characteristic absorbance spectrum.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, when betanine was incubated in basic solutions at 75 °C (Fig 1), the shoulder was already present 15 min after initiating the treatment, and it became the maximum peak in the absorption spectrum after 90 min (data not shown). The degradation of betanine leads to the formation of CDG and BA as products15, 19 (Scheme ). It is known that the amount of betanine that can be regenerated after heating is a function of both the pH and the presence of BA and CDG in the reaction media 3.…”
Section: Resultsmentioning
confidence: 99%
“…These were separated by elution with 50 m M phosphate buffer, pH 7.0, through a Sephadex G‐25 column at a flow rate of 1 ml min −1 as described by Escribano et al 8 The eluate was collected in 2 ml fractions, and betacyanin concentrations (as betanine) were calculated using ϵ 1% = 1120 at 537 nm 18. High‐pressure liquid chromatography (HPLC) analysis19 revealed that betanine was the only component of the betacyanin fractions. The chromatograms were run with methanol/water mobile phase, and detailed operating conditions for analysis were as described by Martinez‐Parra and Muñoz 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18−20 In ref 15, three oxidations of Bt were detected at 0.62, 0.84, and 1.2 V NHE, whereas two oxidations of In were observed at 0.84 and 1.2 V. This indicates that the first oxidation of Bt involves the aromatic ring or the sugar group. 21 An early study by Martı́nez-Parra and Munõz 13 used horseradish peroxidase to oxidize betanin and found an oxidation intermediate with an absorption maximum similar to that of betanin (∼530 nm) and a yellow final oxidation product (λ max = 446 nm), which they assigned to betalamic acid. However, more recent studies assign λ max of betalamic acid to be about 420 nm.…”
Section: ■ Introductionmentioning
confidence: 99%